(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose of the study: The present study aimed to describe the Qur’anic and narrative[1] strategies for dealing with public problems, pandemic, and contagious diseases[2]. Methodology: This study was conducted by collecting reliable Qur’anic and hadith sources[3] and analyzing them using the descriptive-analytical[4] method, and investigating the implicational[5] aspect of the verses[6] and the hadiths. Findings: The analysis of the hadith sources indicated that during the public problems, particularly in the pandemic and contagious diseases, it is recommended to visit a physician, not to leave our homes and cities, and not to travel to the cities where the disease has spread. Moreover, at different times, particularly during the difficulties, we are recommended to pray to God Almighty[7]. Conclusion: The study’s finding showed no inconsistency[8] between the revelatory teachings[9], including the verses and narratives on human health, and the reliable scientific findings; however, the revelatory teachings have recommended us to pray to God and deemed it necessary frequently.